In mathematics, a function f,
![{\displaystyle f:\quad \mathbb {R} ^{n}\rightarrow \mathbb {R} }](https://wikimedia.org/api/rest_v1/media/math/render/svg/f912a9e0a69aa7489502e199a4623be2e1e1b8c4)
is homogeneous of degree p, if
![{\displaystyle f(\lambda \mathbf {x} )=\lambda ^{p}f(\mathbf {x} ),\quad \mathbf {x} \in \mathbb {R} ^{n},\quad \lambda \in \mathbb {R} ,\quad p\in \mathbb {N} ^{*}.}](https://wikimedia.org/api/rest_v1/media/math/render/svg/a72c76553f90e356ec49dc3440e2a6045f7317f6)
The degree of homogeneity p is a positive integral number.
Examples
![{\displaystyle {\begin{aligned}f(x)=&\;ax^{m}\Longrightarrow f(\lambda x)=a(\lambda x)^{m}=\lambda ^{m}(ax^{m})=\lambda ^{m}f(x)\quad ({\hbox{degree}}\;m).\\f(x,y,z)=&\;x^{2}yz+3xy^{2}z-5xyz^{2}\Longrightarrow f(\lambda x,\lambda y,\lambda z)=\lambda ^{4}x^{2}yz+3\lambda ^{4}xy^{2}z-5\lambda ^{4}xyz^{2}=\lambda ^{4}f(x,y,z)\quad ({\hbox{degree}}\;4)\\\end{aligned}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/fc59372a21267cf64c59c71472de07523d46db53)
Euler's theorem
Let f be differentiable and homogeneous of order p, then
![{\displaystyle \sum _{i=1}^{n}x_{i}{\frac {\partial f(x_{1},\dots ,x_{n})}{\partial x_{i}}}=pf(x_{1},\dots ,x_{n})}](https://wikimedia.org/api/rest_v1/media/math/render/svg/24fbb8c7ac401d0b388ffa07a268b657134e9061)
Proof
By the chain rule
![{\displaystyle {\frac {df(\lambda x_{1},\ldots ,\lambda x_{n})}{d\lambda }}=\sum _{i=1}^{n}{\frac {\partial f(\lambda x_{1},\dots ,\lambda x_{n})}{\partial (\lambda x_{i})}}{\frac {d\lambda x_{i}}{d\lambda }}=\sum _{i=1}^{n}x_{i}{\frac {\partial f(\lambda x_{1},\dots ,\lambda x_{n})}{\partial (\lambda x_{i})}}.\qquad \qquad \qquad (1)}](https://wikimedia.org/api/rest_v1/media/math/render/svg/d2cdde898a52e78f62859f99874bbf4da43d7c95)
From the homogeneity,
![{\displaystyle {\frac {df(\lambda x_{1},\ldots ,\lambda x_{n})}{d\lambda }}={\frac {d\lambda ^{p}}{d\lambda }}f(x_{1},\dots ,x_{n})=p\lambda ^{p-1}f(x_{1},\dots ,x_{n}).\qquad \qquad \qquad \qquad \qquad \qquad (2)}](https://wikimedia.org/api/rest_v1/media/math/render/svg/dd2dfcfa2bef448e62d704b5d51f6dfcce355b96)
Compare Eqs (1) and (2) for λ = 1 and the result to be proved follows.